Committees as Active Audiences: Reputation Concerns and Information Acquisition - Otto H. Swank; Bauke Visser (Tinbergen Institute, 2018)
We study committees that acquire information, deliberate and vote. A member cares about state-dependent decision payoffs and about his reputation for expertise. The state remains unobserved, even after the decision has been taken. In such inconclusive environments, in equilibrium, a member's internal (peer) reputation is based on deliberation patterns, while members' external (market) reputation is based on the observed group decision. Either form of reputation concerns create strategic complementarity among members' effort levels. Internal reputations create stronger incentives to become informed than external reputations, and their strength grows in committee size; external reputations create no incentives in large committees. If prior information favors a state, internal – not external – reputations may hinder deliberation. In equilibrium, reputation concerns lead to additional information acquisition without affecting the expected reputations. Nevertheless, moderate rates of reputation concerns relax members' participation constraints, by counteracting the often predicted underprovision of information in committees.
Keywords: D71; D83; 330; committee decision making; reputation concerns; information acquisition; peers; markets